Simple Bookkeeping Training at the Rembun Village Farmer Group, Dampit, Kabupaten Malang - Yogatama, Ahmad Nizar; Hanif, Rifki; Sidi, Agus Purnomo; Anjaningrum, Widiya Dewi; Cahyaningtyas, Fadilla; Dura, Justita (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The training activity entitled